2015
DOI: 10.1002/elps.201400580
|View full text |Cite
|
Sign up to set email alerts
|

Microchip electrophoresis‐single wall carbon nanotube press‐transferred electrodes for fast and reliable electrochemical sensing of melatonin and its precursors

Abstract: In the current work, single-wall carbon nanotube press-transferred electrodes (SW-PTEs) were used for detection of melatonin (MT) and its precursors tryptophan (Trp) and serotonin (5-HT) on microchip electrophoresis (ME). SW-PTEs were simply fabricated by press transferring a filtered dispersion of single-wall carbon nanotubes on a nonconductive PMMA substrate, where single-wall carbon nanotubes act as exclusive transducers. The coupling of ME-SW-PTEs allowed the fast detection of MT, Trp, and 5-HT in less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…SWCNTs filtered on a non-conductive PMMA substrate acted as transducers. This system resulted in rapid detection of melatonin, tryptophan and serotonin in periods shorted than 150 s (Gomez et al 2015). Furthermore, it was found that an amperometric sensor could be made of CNTs and ferrocene (as a redox-responsive reporter) that was applied in order to detect pathogenic viral DNA from hepatitis C and genomic DNA from Myocobacterium tuberculosis with high sensitivity (Zribi et al 2016).…”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…SWCNTs filtered on a non-conductive PMMA substrate acted as transducers. This system resulted in rapid detection of melatonin, tryptophan and serotonin in periods shorted than 150 s (Gomez et al 2015). Furthermore, it was found that an amperometric sensor could be made of CNTs and ferrocene (as a redox-responsive reporter) that was applied in order to detect pathogenic viral DNA from hepatitis C and genomic DNA from Myocobacterium tuberculosis with high sensitivity (Zribi et al 2016).…”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…In this sense, the most used ones not only in electrochemical sensing, but also as detectors coupled to ME and CE have been CNTs and GP . On the one hand, CNTs, differently from wires described in the following section, are rolled cylinders consisting of one layer of sp 2 carbon‐bonded atoms, single‐walled carbon nanotubes (SWCNTs) or generated by rolling few layers of sp 2 carbon layers, multiwalled carbon nanotubes (MWCNTs) .…”
Section: Carbon Nanostructures In Ce and Mementioning
confidence: 99%
“…These electrodes allow high resistance to fouling, and good stability of the press‐transferred films in PMMA substrates, as shown in Fig. C, in a clinical application of these detectors for the determination of melatonin, its precursor tryptophan, and its derivative serotonin 5‐hydroxytryptamine . Press transfer electrodes have been also used in the food‐chemistry sector for the isoflavone index determination based on the comigration of the total glycosides and total aglycones in soy samples .…”
Section: Carbon Nanostructures In Ce and Mementioning
confidence: 99%
“…Microfluidics‐based systems such as microchip electrophoresis (ME) offer advantages over macro‐scale platforms that include portability, lower consumption of reagents and samples, miniaturized dimensions, faster analysis, and reduced waste generation . ME devices can be fabricated using several materials such as silicon, glass, PMMA, and PDMS .…”
Section: Introductionmentioning
confidence: 99%